In vitro screening of rice landraces for increased drought tolerance at early growth stages using Polyethylene glycol (PEG 6000) - Karanjit, Ritika; Khakural, Aashish; Kandel, Bishnu Prasad (Journal of Agriculture and Natural Resources, 2024)
Drought stress at germination stage can negatively impact the emergence and uniformity of seedlings leading to poor seedling establishment. Screening for drought tolerance at germination stage helps to identify potential rice germplasm tolerant to water scarcity during early growth. An experiment was conducted at the laboratory of Department of Agronomy, Institute of Agriculture and Animal Science (IAAS), Lamjung Campus, Nepal from 18th to 27th July 2023 in order to assess the seed germination of 20 rice landraces under drought stress condition. The experiment was carried out in a two factorial Completely Randomized Design (CRD) with three replications. The genotypes were evaluated against three levels of drought stress simulated at three concentrations of Polyethylene glycol (PEG 6000) @ 0% (Control), 10% and 20%. 20% PEG condition significantly (p≤0.05) recorded the lowest values for Germination Percentage (82%), Vigor Index (443.65), Coefficient of Velocity of Germination (9.91), Germination Index (160.78), Root Length (3.63 cm), Shoot Length (1.67 cm) and the highest values for Mean Germination Time (3.22 days) and Root-Shoot ratio (2.67 cm). Conversely, Control exhibited the fastest Mean Germination Time (1.75 days) and highest Germination Index (219.7). Highest Vigor Index (1329.35) and Shoot Length (7.83 cm) along with lowest Root-Shoot ratio (0.80 cm) was noted in 10% PEG. The Control and 10% PEG were statistically at par for parameters Germination Percentage and Root Length. Genotype Manamure significantly exhibited the highest Germination Index (224.33) and the fastest Mean Germination Time (1.67 days) whereas genotype Rato Anadi Lamcho showed an inferior performance with the lowest Vigor Index (786.37), Germination Index (146.78) and the slowest Mean Germination Time (3 days). Genotype Pahele was observed with maximum values of Germination Percentage (94.67%), Vigor Index (726.8), Germination Index (198.33), Shoot Length (2.713) and fastest Mean Germination Time (2.38 days) under 20% PEG condition. Using PEG 6000 to assess early growth traits is a cost-effective approach in achieving rapid screening for tolerant rice germplasm.